An efficient total synthesis of a natural Penipanoid A. (2nd February 2022) - Reddy, A. Satyanarayana; Reddy, V. Krishna; Rao, G. Nageswara; Basavaiah, K.
Graphical abstract: Abstract: Natural products with heterocyclic core units are ample and widespread in nature, with many compounds exhibiting promising therapeutic properties. Penipanoid A (1 ) is a triazole based natural product isolated from the marine sediment derived fungus Penicillium Aneum SD-44 and exhibits the cytotoxicity and antimicrobial activity. Structurally, it features a 1, 2, 4-triazole motif. Herein, we report an efficient total synthesis of Penipanoid A (1 ) by a multi-component reaction involving formation of a triazole ring system as the key fragment starting from 4-methoxyphenyl acetic acid. Deprotection of the methoxy protected compound 2 provided the required natural product 1 .